The urgency of flipped classroom learning by integrating android-based multimedia to support digital literacy skills of elementary school students - Dewi, Candra; Soetjipto, Budi Eko; Utaya, Sugeng; Suhartadi, Syarif; Rohmanurmeta, Fauzatul Ma’rufah (Edelweiss Applied Science and Technology, 2025)
This research aims to determine the urgency of implementing flipped classroom learning integrated with Android-based multimedia to support elementary school students’ digital literacy skills. Conditions in the field show that existing learning uses something other than learning media that can also support digital literacy capabilities. The application of flipped classroom learning integrated with multimedia is aimed at fifth-grade elementary school students aged 9-12 years. The research method used is mixed. The research began by exploring data in the form of qualitative data and then developing it using quantitative data. The respondents of this research were 164 fifth-grade elementary school students. The sample was selected using a cluster random sampling technique; the researcher divided the population into several groups. Research findings show that flipped classroom learning integrated with interactive multimedia learning is needed for elementary school students classified as digital natives. Teachers, as educators, need to integrate digital-based media into implementing flipped classroom learning both outside and inside the classroom.